Junie B., first grader (at last!) - Park, Barbara; Brunkus, Denise (New York : Scholastic, 2002)
Junie B. thinks first grade is a flop when her kindergarten friend Lucille prefers the company of twins Camille and Chenille and Junie B. needs glasses.
H
"A Stepping stone book."
b
b
Keywords: Schools -- Fiction; Eyeglasses -- Fiction; Friendship -- Fiction